Perfekt unperfekt Elaboration und Imperfektion in der Rhetorik des Designs - Schneller, Annina (Rhetorik-Forschungen, 2021)
The book offers insight into the classical rhetorical strategies of elaboration for researchers interested in rhetoric as well as for designers and artists. The process of elaboration is governed by the tension between the perfect and imperfect, polish and rawness, and by the realization of an ideal or departure from it. The book illustrates this process with regard to the history of graphic design and based on two case studies.